2015
DOI: 10.1002/chem.201405812
|View full text |Cite
|
Sign up to set email alerts
|

Radiofluorination of a Pre‐formed Gallium(III) Aza‐macrocyclic Complex: Towards Next‐Generation Positron Emission Tomography (PET) Imaging Agents

Abstract: As part of a study to investigate the factors influencing the development of new, more effective metal-complex-based positron emission tomography (PET) imaging agents, the distorted octahedral complex, [GaCl(L)]⋅2 H2O has been prepared by reaction of 1-benzyl-1,4,7-triazacyclononane-4,7-dicarboxylic acid hydrochloride (H2L⋅HCl) with Ga(NO3)3⋅9 H2O, which is a convenient source of GaIII for reactions in water. Spectroscopic and crystallographic data for [GaCl(L)]⋅2 H2O are described, together with the crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
2
25
0
3
Order By: Relevance
“…This research builds on the use of complexes of group‐13 metals to form high affinity complexes with [ 18 F]fluoride, driven with a goal for the development of lipophilic radiolabeled complexes which may have applications of neuroimaging. Whilst Bhalla et al reported the preparation of the first Ga‐ 18 F complexes, they did not report the properties of their complexes in vivo. This paper describes the first example of in vivo imaging of a Ga‐ 18 F compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research builds on the use of complexes of group‐13 metals to form high affinity complexes with [ 18 F]fluoride, driven with a goal for the development of lipophilic radiolabeled complexes which may have applications of neuroimaging. Whilst Bhalla et al reported the preparation of the first Ga‐ 18 F complexes, they did not report the properties of their complexes in vivo. This paper describes the first example of in vivo imaging of a Ga‐ 18 F compound.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds form a square pyramidal structure, raising the possibility of introducing positron emitting isotopes easily using a halogen exchange strategy. Although this method of introducing fluorine‐18 has been explored by McBride et al and Bhalla et al using different metal chelate moieties, the complexes generated by these groups are all hydrophilic. In contrast, gallium‐ 18 F complexes of dithiosemicarbazones will be both lipophilic and neutral.…”
Section: Introductionmentioning
confidence: 99%
“…[88] Recently,n ew chelators for the formation of 18 F À Al complexes were developed by Bormans and co-workers to address heatsensitive biomolecules.T he new acyclicp olydentate ligands were less rigid than macrocyclic NOTA,w hich substantially reduced the activation energy for AlÀFcomplexation. [194][195][196] Fore xample,[ 18 F]GaF 3 (BnMe 2 -tacn) could be obtained by 19 F/ 18 F exchange in high RCY (81 AE 1%;Scheme 33 D). [192,193] Recently Reid and co-workers developed ac helating strategy for the preparation of as eries of 18 F-labeled Ga compounds through halogen- 18 Fe xchange.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We propose and demonstrate an approach to optimize radiochemical reactions by tracer‐level (nanomolar) [ 19 F]KF and quantitation using liquid chromatography/tandem mass spectrometry (LC‐MS/MS). Optimizing radiochemical reactions with natural isotope has been a known approach for decades, which helped radiochemists to establish radiolabeling conditions . But to our knowledge, no quantitation method at no‐carrier‐added (NCA) level has been reported, primarily due to the lack of available analytical methods to quantify tracer‐level of product.…”
Section: Introductionmentioning
confidence: 99%